Home care for patients with dirty homes: a qualitative study of the problems experienced by nurses and possible solutions - Anke J. E. De Veer; Kim De Groot; Renate Verkaik (BMC, 2022)
Abstract Background Home-care nurses are often the first care professionals to enter a dirty home. The perceived problems and support needs of home-care nurses in these situations are largely unknown. Objective To examine the problems home-care nurses encounter in caring for patients living in dirty homes, and possible solutions for these problems. Design Qualitative descriptive research. Setting Communities across the Netherlands. Participants Twenty-three participants to investigate the problems or needs experienced, and 20 participants to investigate solutions. Participants included patients, home-care nurses and other professionals working in the community. Methods Semi-structured interviews were conducted with 23 participants and analysed according to the principles of deductive thematic analysis. Subsequently, in interviews with 4 (representatives of) patients and four focus-group sessions with 16 professionals, the problems found were validated and solutions to the problems discussed. Results Ten subthemes emerged that were clustered into three main themes: 'dilemmas arise in choosing the right nursing care'; 'cooperation and an integrated approach are often necessary, but lacking'; 'home-care nurses have insufficient competencies'. Seven possible solutions were found: (1) strengthening collaboration between organizations in the community; (2) involving others sooner; (3) case management; (4) person-centred care; (5) taking more time; (6) providing home-care nurses with tools and support services; and (7) strengthening the competencies of nurses. Conclusions Care for patients with a dirty home is complex. An integrated person-centred care approach is often necessary and home-care nurses need extra support to provide such care. Interventions should not only focus on patients, but address the nurses, the organization, and the collaboration between organizations in the community.